Polemik Memakan Darah: Studi Kasus dalam Sidang di Yerusalem - Walean, Jefrie (Sekolah Tinggi Teologi Kalvari Manado, 2022)
Abstract: This study aims to find answers to the controversy about halal and haram eating blood based on investigations in the trial in Jerusalem. The polemic of eating blood has become a theological controversy among Christians from time to time. Controversy due to differences of opinion because it has a background of diverse theological assumptions. This polemic can actually be resolved if the relational perception is a win-win solution. Is in today's life the prohibition on eating blood in the Old Testament still applies and is it still a disaster for mankind? This study uses a qualitative method with library research and analysis using the principles of hermeneutic interpretation. This study concludes that the doctrinal culmination point related to the blood-eating polemic is one of the factors that breaks relations between Christian groups so that it becomes an interesting